Sodium channel expression in the ventral posterolateral nucleus of the thalamus after peripheral nerve injury - Waxman Stephen G; Zhao Peng; Hains Bryan C (SAGE Publishing, 2006)
Abstract Peripheral nerve injury is known to up-regulate the expression of rapidly-repriming Nav1.3 sodium channel within first-order dorsal root ganglion neurons and second-order dorsal horn nociceptive neurons, but it is not known if pain-processing neurons higher along the neuraxis also undergo changes in sodium channel expression. In this study, we hypothesized that after peripheral nerve injury, third-order neurons in the ventral posterolateral (VPL) nucleus of the thalamus undergo changes in expression of sodium channels. To test this hypothesis, adult male Sprague-Dawley rats underwent chronic constriction injury (CCI) of the sciatic nerve. Ten days after CCI, when allodynia and hyperalgesia were evident, in situ hybridization and immunocytochemical analysis revealed up-regulation of Nav1.3 mRNA, but no changes in expression of Nav1.1, Nav1.2, or Nav1.6 in VPL neurons, and unit recordings demonstrated increased background firing, which persisted after spinal cord transection, and evoked hyperresponsiveness to peripheral stimuli. These results demonstrate that injury to the peripheral nervous system induces alterations in sodium channel expression within higher-order VPL neurons, and suggest that misexpression of the Nav1.3 sodium channel increases the excitability of VPL neurons injury, contributing to neuropathic pain.